Enhancing Conceptual Understanding of Buffer Solutions with an Intertextual E-Book Prototype - Nur Sehasari Dewi; Sri Mulyani; Wiji wiji (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
The intertextual-based e-book prototype helps students understand buffer solutions by connecting the three levels of chemical representation: macroscopic, submicroscopic, and symbolic. This connection allows students to visualize chemical phenomena from simple to complex. The study aims to enhance students' conceptual understanding using this e-book prototype. The research and development (R&D) method followed five stages: research and information gathering, product development planning, initial product development, limited trials, and initial product revision. This process yielded a highly validated e-book prototype that promotes innovation. The validation results showed high feasibility in substance (85.71%), instructional methods (90.90%), and language (100%). Experts deemed the e-book prototype highly effective in improving conceptual understanding through its intertextual approach. Pretest and posttest assessments of 30 students indicated improved conceptual understanding after using the e-book. Initially, students demonstrated macroscopic and symbolic level abilities without associating the three levels of representation. After using the e-book, they could connect these levels, enhancing their understanding and conceptual understanding. The N_Gain scores for pretest and posttest assessments were 0.48 for the high category, 0.45 for the medium category, and 0.44 for the low category, showing moderate improvement. The t-test results (Sig. (2-tailed) = 0.000 < 0.05) confirmed the effectiveness of the e-Book. Teacher and student responses averaged 90% and 85.5%, respectively, indicating that the intertextual-based e-book on buffer solutions is highly suitable as a self-learning resource to improve conceptual understanding.